2014
DOI: 10.2337/dc14-1459
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-Based Drugs and the Risk of Congestive Heart Failure

Abstract: OBJECTIVETo determine whether the use of incretin-based drugs, including GLP-1 analogs and dipeptidyl peptidase-4 inhibitors, is associated with an increased risk of congestive heart failure (CHF) among patients with type 2 diabetes. RESEARCH DESIGN AND METHODSThe U.K. Clinical Practice Research Datalink, linked to the Hospital Episode Statistics database, was used to conduct a cohort study with a nested case-control analysis among patients newly prescribed antidiabetic drugs between 1 January 2007 and 31 Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
2
43
0
2
Order By: Relevance
“…Prior observational studies (12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) that assessed the association between hHF and either the DPP-4i agents as a class or specific DPP-4i agents (i.e., sitagliptin) have used a wide variety of designs and patient populations with mixed results. Two studies (12,18) identified that DPP-4i treatment is associated with a reduced rate of hHF relative to other oral antihyperglycemic medications, two studies (14,16) suggested a neutral association relative to other oral antihyperglycemic medications and/or insulin, and two studies (19,20) suggested an increased rate of hHF with DPP-4i treatment relative to matched control subjects not otherwise initiating a new antihyperglycemic medication but rather in the midst of treatment with any of a range of potential antihyperglycemic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Prior observational studies (12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) that assessed the association between hHF and either the DPP-4i agents as a class or specific DPP-4i agents (i.e., sitagliptin) have used a wide variety of designs and patient populations with mixed results. Two studies (12,18) identified that DPP-4i treatment is associated with a reduced rate of hHF relative to other oral antihyperglycemic medications, two studies (14,16) suggested a neutral association relative to other oral antihyperglycemic medications and/or insulin, and two studies (19,20) suggested an increased rate of hHF with DPP-4i treatment relative to matched control subjects not otherwise initiating a new antihyperglycemic medication but rather in the midst of treatment with any of a range of potential antihyperglycemic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have attempted to assess the association between the use of DPP-4 inhibitors and hospitalization for HF (25)(26)(27)(28)(29) (Table 1). The studies have generally used propensity score matching, with varying success at matching the groups, and applied a Cox proportional hazards model or a conditional logistic regression to adjust for further confounding.…”
Section: Dpp-4 Inhibitors and Hf: Evidence From Observational Studiesmentioning
confidence: 99%
“…Данные крупных регистров, основанных на анализе частоты развития сердечно-сосудистых событий и СН при лечении пациентов с СД2 иДПП-4 в сравнении с другими антидиабетическими препаратами, показали сопоставимую частоту развития сердечно-сосудистых событий и госпитализаций, связанных с СН [37]. Таким образом, вопрос о влиянии иДПП-4 на развитие или те-чение СН на основании имеющихся данных остается открытым.…”
Section: сахарный диабет Diabetes Mellitusunclassified